Methodological Basis of The Problem of Psychological Properties of Individual Professional Competence - Usmonova Xusnora Ergashovna (Zien Journals, 2022)
A person’s professional competence is focused on spiritual, motivational, intellectual and practical self-development, willpower and emotional self-management. Each member of society has his own interests and abilities, which allows him to develop the personal and professional qualities of a modern specialist,helps shape their thinking, culture, and behavior. He played an important role in the organization of professional activities
Keywords: activities; professional; emotional; motivational